Pemetaan Kesiapan Penerapan Telemedika di Indonesia - Nora Dzulvawan; Setia Pramana (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractTelemedicine is a form of technology development that allows people to conduct health consultations without having to physically visit the hospital. The COVID-19 pandemic that has spread throughout the world has increasingly limited human mobility and has implications for the application of technology. In addition, the vulnerability of public health during the pandemic has caused hospitals to treat patients with quite limited medical personnel. One of the solutions to overcome the crisis is to use technology in the health sector. However, Indonesia's diverse geographical situation presents its own challenges for the development of telemedicine. In addition, health facilities that are not evenly distributed also have a significant influence on the development of telemedicine. This study aims to prepare provinces in Indonesia for the development of telemedicine in terms of medical infrastructure and Information and Communications Technology (ICT). The K-Means Cluster is used as the primary method for grouping each province based on these two aspects. The result is 3 clusters of Indonesian provinces which are then defined as regions with a very ready status, ready, and not ready for the development of telemedicine in Indonesia. From the results of the analysis, it was found that the most influential variable in the development of telemedicine in Indonesia is the readiness of the ICT and health workers. Thus, it can be said to develop telemedicine or e-health in Indonesia, the improvement of Information and Communication Technology infrastructure, and the increment in natural resources and human resources in the medical field are needed, so the development of telemedicine can support improving the health status of Indonesian people.Keyword: digital health, K-Means cluster, ICT AbstrakTelemedika adalah bentuk pengembangan teknologi yang memungkinkan seseorang melakukan konsultasi kesehatan tanpa perlu mendatangi rumah sakit secara fisik. Pandemi COVID-19 yang menyebar di seluruh dunia semakin membatasi ruang gerak manusia dan berimplikasi pada pemanfaatan teknologi yang semakin tinggi. Selain itu rentannya kesehatan masyarakat di masa pandemi menyebabkan rumah sakit mengalami lonjakan pasien dengan tenaga medis yang cukup terbatas. Salah satu solusi untuk mengatasi krisis tersebut adalah dengan pemanfaatan tekonologi di bidang kesehatan. Namun keadaan geografis Indonesia yang cukup beragam memberikan tantangan tersendiri terhadap perkembangan telemedika. Selain itu, fasilitas kesehatan yang belum merata juga memberikan pengaruh cukup signifikan terhadap kemajuan telemedika. Penelitian ini bertujuan untuk memetakan kesiapan provinsi di Indonesia dalam pengembangan telemedika dilihat dari aspek infrastruktur medis dan Information and Communications Technology (ICT). Metode K-Means Clustering dijadikan sebagai dasar pengelompokan provinsi berdasarkan kedua aspek tersebut. Hasilnya adalah didapatkan tiga klaster provinsi Indonesia yang kemudian didefinisikan menjadi wilayah dengan status sangat siap, siap, dan tidak siap dalam perkembangan telemedika di Indonesia. Dari hasil analisis didapatkan variabel yang paling berpengaruh terhadap perkembangan telemedika di Indonesia adalah kesiapan dari sisi ICT dan tenaga kesehatan. Dengan demikian dapat disimpulkan untuk melakukan pengembangan telemedika atau e-health di Indonesia, perbaikan infrastruktur Teknologi Informasi dan Komunikasi dan peningkatan SDA maupun SDM di bidang medis sangat dibutuhkan sehingga pengembangan telemedika dapat menjadi salah satu penunjang perbaikan status kesehatan masyarakat Indonesia.Kata Kunci: digital health, K-Means Cluster, ICT